Intermittent Resistance Exercise: Evolution from the Steady State - Christopher B. Scott (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2014)
Oxygen uptake measurements are without question useful and a staple measurement for the estimation of exercise energy costs. However, steady state models cannot be used to successfully model intermittent resistance exercise energy costs. Our laboratory has taken steps to avoid such comparisons between these discrepant exercises. We have separated out exercise and recovery periods during resistance training and utilize capacity (kJ) estimates as opposed to rate measures (kJ min-1). Moreover, we avoid anaerobic threshold concepts as applied to resistance exercise. When viewed accordingly, resistance exercise energy costs are opposite those of the steady state model: exercise oxygen uptake is highest for steady state exercise and lowest for resistance exercise, recovery oxygen uptake can be the highest energy cost for resistance exercise whereas for steady state exercise it may or may not be meaningful, and anaerobic energy costs represent a significant component of resistance exercise that plays little to no role with steady state exercise.